If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12(x + -12) = -9(1 + 8x) Reorder the terms: -12(-12 + x) = -9(1 + 8x) (-12 * -12 + x * -12) = -9(1 + 8x) (144 + -12x) = -9(1 + 8x) 144 + -12x = (1 * -9 + 8x * -9) 144 + -12x = (-9 + -72x) Solving 144 + -12x = -9 + -72x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '72x' to each side of the equation. 144 + -12x + 72x = -9 + -72x + 72x Combine like terms: -12x + 72x = 60x 144 + 60x = -9 + -72x + 72x Combine like terms: -72x + 72x = 0 144 + 60x = -9 + 0 144 + 60x = -9 Add '-144' to each side of the equation. 144 + -144 + 60x = -9 + -144 Combine like terms: 144 + -144 = 0 0 + 60x = -9 + -144 60x = -9 + -144 Combine like terms: -9 + -144 = -153 60x = -153 Divide each side by '60'. x = -2.55 Simplifying x = -2.55
| 2(q*q*q)-12(q*q)-43200=0 | | 4=3.2+b | | 10-2x=2x+7+x | | 49(2n+5)=37(3n+1) | | 15+6z=9 | | 49(2n+5)=37(n+1) | | 1/3*12/x-8=-1 | | 45(8n-3)=19(2n+7) | | 2z^2-4z+4=0 | | 16=2x+5y | | y=5ln(3x-2) | | x^2+2*x-3=0 | | y=tan(3+X) | | 8x*1,4=4x | | 9m-13=-8 | | 4a+(-3)-2a=-4a-3 | | 6(x-3)=2 | | 4(8+x)=50 | | -2(5c+6)=8(3-c) | | (1/5)*x=1/125 | | 1/3x=1/9 | | 8x-(3x+6)=15 | | 7x^2+48x+68=0 | | 16b-60=5(5b-3) | | -8t+7=-7t+4 | | 1/3x=-1/3 | | .45x+.85x+12=1.05x | | -x^2+3=4x-1 | | 9n-9-3n= | | x^2+4xy-4x=0 | | (x-6)+(y+7)=85 | | 2x+900=2 |